From coarse to fine: the absolute Escherichia coli proteome under diverse growth conditions. Issue 5 (25th May 2021) - Mori, Matteo; Zhang, Zhongge; Banaei‐Esfahani, Amir; Lalanne, Jean‐Benoît; Okano, Hiroyuki; Collins, Ben C; Schmidt, Alexander; Schubert, Olga T; Lee, Deok‐Sun; Li, Gene‐Wei; Aebersold, Ruedi; Hwa, Terence; et al.
Abstract: Accurate measurements of cellular protein concentrations are invaluable to quantitative studies of gene expression and physiology in living cells. Here, we developed a versatile mass spectrometric workflow based on data‐independent acquisition proteomics (DIA/SWATH) together with a novel protein inference algorithm (xTop). We used this workflow to accurately quantify absolute protein abundances in Escherichia coli for > 2, 000 proteins over > 60 growth conditions, including nutrient limitations, non‐metabolic stresses, and non‐planktonic states. The resulting high‐quality dataset of protein mass fractions allowed us to characterize proteome responses from a coarse (groups of related proteins) to a fine (individual) protein level. Hereby, a plethora of novel biological findings could be elucidated, including the generic upregulation of low‐abundant proteins under various metabolic limitations, the non‐specificity of catabolic enzymes upregulated under carbon limitation, the lack of large‐scale proteome reallocation under stress compared to nutrient limitations, as well as surprising strain‐dependent effects important for biofilm formation. These results present valuable resources for the systems biology community and can be used for future multi‐omics studies of gene regulation and metabolic control in E .  coli . Synopsis: Accurate proteomic measurements of absolute protein mass fractions in Escherichia coli allowed the characterization of proteome responses under > 60 diverse growth conditions from a coarse (groups of related proteins) to a fine (individual) protein level. The study presents a mass spectrometric workflow based on data‐independent acquisition proteomics and a novel protein inference algorithm (xTop) optimized for absolute protein quantification. The mass spectrometric data was benchmarked and calibrated with absolute protein mass fractions obtained by ribosome profiling. A plethora of novel biological findings are presented, including lack of large‐scale proteome reallocation under stress compared to nutrient limitations, regulation of outer membrane proteins, and effects important for motility and biofilm formation. Abstract : Accurate proteomic measurements of absolute protein mass fractions in Escherichia coli allowed the characterization of proteome responses under > 60 diverse growth conditions from a coarse (groups of related proteins) to a fine (individual) protein level.